1993
DOI: 10.1002/art.1780360307
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of serious liver disease among patients receiving low‐dose methotrexate for rheumatoid arthritis

Abstract: Objective. To assess the risk of serious liver disease in patients with rheumatoid arthritis (RA) taking methotrexate (MTX).Methods. We surveyed members of the American College of Rheumatology to determine previous use of MTX in the treatment of rheumatoid arthritis and to identify cases of cirrhosis and liver failure. Cases were confirmed by review of pathology specimens, findings from diagnostic testing, and clinical presentations. A caswontrol study was then conducted to ascertain prognostic factors. Case a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
85
0
2

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 175 publications
(98 citation statements)
references
References 12 publications
5
85
0
2
Order By: Relevance
“…The ACR survey confirmed that liver enzyme values were likely to be abnormal in MTX-treated RA patients who developed clinically significant liver disease (10).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…The ACR survey confirmed that liver enzyme values were likely to be abnormal in MTX-treated RA patients who developed clinically significant liver disease (10).…”
mentioning
confidence: 73%
“…More recently, case reports have described significant liver disease in RA patients receiving MTX (6-9). A survey of the membership of the American College of Rheumatology (ACR) identified another 24 cases of cirrhosis and liver failure in patients with RA who had received therapy with the drug (10).…”
mentioning
confidence: 99%
“…However, as experience with the use of this drug in rheumatoid arthritis increased, it became apparent that liver toxicity was not common (8,9). While it is difficult to estimate risk, a 5-year cumulative incidence of cirrhosis was -1/1,000 treated patients in l retrospective study (9).…”
Section: Discussionmentioning
confidence: 98%
“…Many risk factors such as age, duration of exposure to MTX and its cumulative dose, history of Non Alcoholic Steatohepatitis (NASH), diabetes and obesity, hepatitis B or C virus infection, alcohol consumption and hepatotoxic drugs can increase the hepatotoxic effect of MTX (Lorenz and Knudtson, 2007;Diouf et al, 2001;Visser et al, 2009;Jones and Patel, 2000;Kremer et al, 1995;Langman et al, 2001;Leonard et al, 1987;Malatjalian et al, 1996;Reynold and Lee, 1986;Salliot, C. and Heijde D.V.D., 2009;Walker et al, 1993).…”
Section: Introductionmentioning
confidence: 99%